2013
DOI: 10.1249/mss.0b013e31827d87ec
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Cardiovascular Disease in African Americans in Atherosclerosis Risk in Communities

Abstract: Purpose Although there is substantial evidence that physical activity reduces a person's risk of cardiovascular disease (CVD), few of these studies have included African Americans. The studies that have included African Americans offer inconclusive evidence on the association and none studied heart failure separately. We used data from the Atherosclerosis Risk in Communities study cohort to examine, in African Americans, the association of physical activity with the incidence of CVD and its major components – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 28 publications
4
82
2
Order By: Relevance
“…However, we had limited power to detect significant associations among the black and Asian men. Bell et al, 37 examining physical activity and cardiovascular disease among blacks in the Atherosclerotic Risk In Communities (ARIC) study, reported similar HRs for HF incidence among blacks and whites after 21 years of follow-up. There are several key differences between ARIC and CMHS cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…However, we had limited power to detect significant associations among the black and Asian men. Bell et al, 37 examining physical activity and cardiovascular disease among blacks in the Atherosclerotic Risk In Communities (ARIC) study, reported similar HRs for HF incidence among blacks and whites after 21 years of follow-up. There are several key differences between ARIC and CMHS cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, we used the results of the original studies from multivariable-adjusted models with the most complete adjustment for potential baseline confounders, including the presence of risk factors such as hypertension, diabetes mellitus, and body mass index for primary analysis. One study 19 reported separate HRs for HF risk associated with different PA levels for blacks and whites. As a result, we included data from both the black and white cohorts separately in the pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In contrast, the role of PA in reducing risk of HF has not been emphasized in existing guidelines and public health recommendations. 15 Although observational cohort studies have reported an inverse association between higher levels of PA and HF risk, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a comprehensive assessment of the quantitative dose-response association between PA and HF risk has not been previously reported. Understanding this relationship is important because recent studies suggest that there may be important differences in the mechanisms through which PA modifies HF risk and CHD risk, 20 and the dose of PA needed to significantly lower HF risk may differ from that currently recommended to reduce CHD risk.…”
Section: Editorial See P 1777 Clinical Perspective On P 1794mentioning
confidence: 99%
“…All the included physical activity studies divided subjects into 2 or 5 groups on the basis of leisure time, [14][15][16] occupational and leisure-time physical activity, 17,18 vigorous physical activity, 19 cumulative/total physical activity. 20,21 For all the studies included, the extreme groups (ie, maximum versus minimal amount of physical activity) were used for the current analyses.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…25,26 The ascertainment of HF was mostly based on hospital or death records, with only 1 study distinguishing type of HF into HF with reduced ejection fraction versus HF with preserved ejection fraction. 17 The degree of covariate adjustment varied across studies, with 8 studies accounting for intermediate states such as coronary heart disease (CHD) either through adjustment 14,18,21,24 or restriction of analyses to those with nonischemic HF 16,20,23 or exclusion of those with CHD at baseline (either as part of the original study design or a subgroup analysis). 19,24 Study quality varied among the included studies.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%